Execução orçamentária: uma análise da arrecadação da receita e da execução da despesa do governo do Estado do Ceará no período de 2008 a 2011 - Leitão Neto, Vicente Ferrer (2013)
In order for the Government to meet the various demands of social nature, it is necessary the existence of a proper planning regarding the application of public resources, as a way to correct the administrative failures, resolve social needs and, consequently, to ensure the viability and implementation of projects and government actions. Under this approach, the Government budget assumes essential role in generating information directed primarily to the control by the part of stakeholders and responsible. Accordingly, this research aims at analyzing the budgetary execution of the Government of State of Ceará in the period 2008 2011. To do so, we used a descriptive and qualitative research, with bibliographical and documentary analysis. The data of this study, namely the reported amounts of revenues and budgetary expenses, were obtained by the collection of the published information in the Balance Sheet of the State of Ceará, in the period of 2008-2011. It was found that in each of the four years observed the federative revenue collection under consideration registered a deficit, caused, primarily, by the effects of the global financial crisis. With respect to costs, there was a gradual growth in public spending due to investments made in the period, which impacted both the increase in capital expenditures as of the current ones. It was observed also that the result in the consolidated budget of the quadrennium recorded a budget surplus, which demonstrates that the state carried out more revenue than expenses, in other words, revenues exceeded the expenditure execution.